1978
DOI: 10.1007/bf01538046
|View full text |Cite
|
Sign up to set email alerts
|

Gender identity in a group of retarded children

Abstract: The Michigan Gender Identity Test (MGIT) was administered to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Research into the concept of gender, which is perhaps related to the concept of age recognition, may help elucidate the process. Abelson & Paluszny (1978) looked at the development of gender recognition in normal children and those with intellectual disability, and found that there was a significant correlation between this ability and mental age for children with intellectual disability. In children from the normal range of intellectual ability, gender identity was correlated significantly with both chronological and mental age, and this was achieved by around 3 years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the concept of gender, which is perhaps related to the concept of age recognition, may help elucidate the process. Abelson & Paluszny (1978) looked at the development of gender recognition in normal children and those with intellectual disability, and found that there was a significant correlation between this ability and mental age for children with intellectual disability. In children from the normal range of intellectual ability, gender identity was correlated significantly with both chronological and mental age, and this was achieved by around 3 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because gender identity correlated with mental age and intellectual ability, Abelson & Paluszny (1978) considered that many children with intellectual disability could learn this concept in time and with additional training, and eventually they could perhaps go on to deal with more difficult concepts such as gender constancy and gender role. The above authors also looked at the cues used to determine gender and these are considered in more detail below.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an uncontrolled study, Abelson (1981) administered the Michigan Gender Identity Test (Paluszny et al, 1973;Dull et al, 1975) to 30 subjects "diagnosed as autistic," and reported that only 11 of the 23 autistic subjects with MA (Leiter) between 25 and 60 months gave "correct MGIT responses" in sorting pictures of girls and boys, whereas in the prior study of Abelson and Paluszny (1978), twothirds of normal and retarded children of similar MA (Stanford-Binet) had succeeded in a corresponding task. The second study (Hobson, 1983b) investigated whether autistic and matched nonautistic retarded children differed in their propensity to sort pictures of people, animals, and nonpersonal things according to age-related characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…Hampson (1957) reported a critical period for gender identity formation occurring between 18 months and 3 years of age. Others agree that by 36 months of age, the sense of being a boy or a girl (the concept of gender identity) is well established (Gesell et al 1940, Paluszny et al 1973, Thompson 1975, Abelson & Paluszny 1978.…”
mentioning
confidence: 99%